Thermodynamic Process and Analysis of Dilution Refrigerator. Issue 1 (1st May 2022) - Zheng, M W; Wei, L J; Pan, Z J; Liang, J T; Zhao, M G; Lin, P
Abstract: Thermodynamic analysis is essential for not only guiding the design of refrigerator, but also studying its operation mechanism. As the core component, the dilution unit plays an important role in deciding the performance of dilution refrigerator. In this study, a coupled thermodynamic model is established by analyzing each component separately for improving the operation of dilution refrigerator. And an optimization calculation based on that model is carried out to obtain some meaningful results on the dilution unit design. The optimal flow rate of the dilution refrigerator under different working conditions are pointed out. By considering the effect of viscous heat on the performance of the heat exchanger, the applicable conditions of the continuous heat exchanger and the methods to overcome the viscous heat are given.